2018
DOI: 10.3389/fpls.2018.00396
|View full text |Cite
|
Sign up to set email alerts
|

Seed and Foliar Application of Amino Acids Improve Variables of Nitrogen Metabolism and Productivity in Soybean Crop

Abstract: The application of amino acids in crops has been a common practice in recent years, although most of the time they are associated with products based on algae extracts or on fermented animal or vegetable wastes. However, little is known about the isolated effect of amino acids on the development of crops. Therefore, the objective of this research was to evaluate the effect of the application of isolated amino acids on the in some steps of the soybean nitrogen metabolism and on productivity. Experiments were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 43 publications
(55 reference statements)
2
37
1
2
Order By: Relevance
“…It has been suggested that ammonia may have a role in antagonism against competing flora, particularly the fungi. These agree with Teixeira et al (2018) who estimated that application amino acids glutamate, cysteine and glycine can act as signaling amino acids in soybean plants. Small doses are enough to increase the activity of the antioxidant enzymes, glutamate stands out for being the first amino acid in which the nitrogen absorbed by the plants a range of amino acids can be obtained through the activity of aminotransferases, In addition, amino acids such as glutamate, cysteine, and glycine may act directly or indirectly in the attenuation of plant oxidative stresses".…”
Section: Qualitative Analysis Of Essential Oilsupporting
confidence: 91%
“…It has been suggested that ammonia may have a role in antagonism against competing flora, particularly the fungi. These agree with Teixeira et al (2018) who estimated that application amino acids glutamate, cysteine and glycine can act as signaling amino acids in soybean plants. Small doses are enough to increase the activity of the antioxidant enzymes, glutamate stands out for being the first amino acid in which the nitrogen absorbed by the plants a range of amino acids can be obtained through the activity of aminotransferases, In addition, amino acids such as glutamate, cysteine, and glycine may act directly or indirectly in the attenuation of plant oxidative stresses".…”
Section: Qualitative Analysis Of Essential Oilsupporting
confidence: 91%
“…Amino acids can also increase transcription of genes involved in nitrate, ammonium, phosphorous, magnesium and iron transport (Santi et al, 2017). Teixeira et al (2018) demonstrated that applying glycine, cysteine and glutamate to seeds or leaves raises nitrate and amino acid accumulation in leaves. These characteristics are essential to plants, since they guarantee better growth and increase photosynthetic area, which leads to higher production of photoassimilates that can be used during the grain-filling phase, resulting in greater yield (Board & Modale, 2005;Soares et al, 2016;Teixeira et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These processes include seed germination, seedling establishment, plant growth, development, senescence, and even response and adaptation to environmental stress, such as salt, cold, heat, drought, wound, and pathogen stress. In soybean crop, foliar or seed application of Glu in both greenhouse and field could enhance the antioxidant capacity by activating antioxidant enzymes catalase, peroxidase, superoxide dismutase, polyphenol oxidase, and phenylalanine ammonia lyase (Teixeira et al, 2017) and improved nitrogen metabolism and productivity (Teixeira et al, 2018). Under drought stress conditions, foliar or seed application of Glu, as stress reducer, increased Pro and relative water content, leaf and root dry weight, and plant productivity (Teixeira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%